Highly efficient field emission properties of radially aligned carbon nanotubes - Tripathi, P.; Gupta, B.K.; Bhatnagar, A; Patel, C.R.P; Banker, P.K.; Late, D.J.; More, M.A.; Lalla, N.P.; Phase, D.M.,; Choudhary, R.J.; Shaz, M.A.; Ajayan, P.M.; et al. (Journal of Materials Chemistry C, 2018)
Here, we report extraordinary field emission properties from one pot synthesized aligned carbon nanotubes endowed with related Fe nanoparticles (NPs). The CNT configuration is in the form of a carbon hollow cylinder (CHC) with CNTs radially aligned towards the CHC axis. The structure generates electron field emission properties such as an ultralow turn on field (0.35 V μm−1 at 10 μA cm−2), a low threshold field (0.41 V μm−1 at 100 μA cm−2) and a high field emission current density (7.71 mA cm−2 at 0.78 V μm−1). It also exhibits multi-fold improvement in the field enhancement factor (1.34 × 104) with highly stable current emission at 100 μA measured for 14 h. No post synthesis treatment is required for enhanced field emission characteristics. The growth related Fe NPs assist in lowering the work function and hence enhancing the field emission properties. The possibility of assembling nano-structured field emitters into macroscale architectures suggests new prospects for next generation three dimensional electron sources.